2017
DOI: 10.1016/j.sjopt.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Chiasmal syndrome: Clinical characteristics in patients attending an ophthalmological center

Abstract: The ophthalmologist participates in the diagnosis and rehabilitation of patients with chiasmal syndrome. Low visual acuity is the most common symptom at presentation, and bitemporal hemianopia the most frequent GVF defect. Examination of the optic nerve head and pupillary responses, and ancillary tests including Ishihara test and neuroimaging are relevant for diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 12 publications
1
6
1
9
Order By: Relevance
“…Dyschromatopsia as tested using Ishihara color plates was seen in all cases (100%), involving 22 eyes. This is higher compared to a study by Astorga 9 , affecting only 62.5% of their cases, which probably is due to the fact that most of the patients presented in the late course of the disease.…”
Section: Chiasmal Syndrome Can Have a Variety Of Clinical Manifestations With Low Vision As The Initial Presentationcontrasting
confidence: 69%
See 1 more Smart Citation
“…Dyschromatopsia as tested using Ishihara color plates was seen in all cases (100%), involving 22 eyes. This is higher compared to a study by Astorga 9 , affecting only 62.5% of their cases, which probably is due to the fact that most of the patients presented in the late course of the disease.…”
Section: Chiasmal Syndrome Can Have a Variety Of Clinical Manifestations With Low Vision As The Initial Presentationcontrasting
confidence: 69%
“…The average Mean Deviation of 22 eyes is 21.79dB (8.3 to 38.45dB). Majority of eyes had MD of more than 10 dB as seen in table 5It is notable that in this case A retrospective study done by Astorga-Carballo et al9 with a larger population than ours (n = 104) observed a slight female predominance (1:1.47) and a median…”
supporting
confidence: 45%
“…A pathological process in the chiasmal and sellar region results in the development of neuro-ophthalmic symptoms of chiasmal syndrome (CS) with decreased visual acuity, visual field defects and development of descending optic nerve atrophy. Other symptoms that may develop in CS include diplopia, impaired color perception, impaired stereoscopic vision, photophobia and a number of generalized symptoms like headache and hormonal abnormalities [5][6][7][8].…”
Section: Paul Bert a French Physiologistmentioning
confidence: 99%
“…Pupil responses are preserved or slightly reduced infrequently. Complete ophthalmoplegia is rare, and most commonly occurs in tumoral hemorrhage [2,6].…”
Section: Intrachiasmal Lesionsmentioning
confidence: 99%
“…Já, as fibras oriundas da retina nasal superior cruzam o quiasma óptico na sua porção mais superior e posterior e são geralmente afetadas por lesões que crescem superiormente a ele, como os craniofaringeomas, causando defeitos temporais inferiores de CV (29) . As fibras maculares geralmente se posicionam na região mais central e superior do quiasma óptico (30) .…”
Section: Anatomia Da Via óPtica Anteriorunclassified